Immunoelectrophoretic comparison ol Trypanosoma vespertilionis and Trypanosoma cruzi - Bice, David E. (1971)
Immunoelectrophoretically, T. vespertilionis showed five of seven antigenic fractions found with T. cruzi antigen, indicating a close similarity between these two species. An antigen made of L. braziliensis promastigotes did not give any precipitation band against T. cruzi antiserum.